The Impact of the Implementation of the Press Law on the Independence of Kabarsinjai.com Online Media - Iskandar, Nurfajar; Yusuf, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the impact of the implementation of the Press Law on the independence of online media, with a case study on kabarsinjai.com. The aim is to analyze the influence of the Press Law on the independence of kabarsinjai.com as a local online media. Using Independence Theory as an analytical framework, this qualitative research explores data through document studies, interviews, and observations. The results show that the implementation of the Press Law has positive and negative impacts on the independence of kabarsinjai.com. The Press Law provides legal protection and press freedom, but there are challenges in its interpretation and application that can affect editorial independence. The research identified various challenges and opportunities in maintaining the independence of online media. Although the Press Law aims to protect press freedom, its implementation in online media requires adjustments to ensure media independence is maintained in the digital era.